2012
DOI: 10.1097/mao.0b013e31825e7e36
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Management of Internal Auditory Canal and Cerebellopontine Angle Facial Nerve Schwannoma

Abstract: Objective To investigate the long-term patient outcomes following tumor debulking for internal auditory canal facial schwannoma (FNS). Study Design retrospective case review Setting Tertiary referral center Patients Patients operated on between 1998–2010 for a preoperative diagnosis of vestibular schwannoma with the intraoperative identification FNS instead. Intervention diagnostic and therapeutic Main Outcome Measures House-Brackmann facial nerve score immediately and at long term follow up (>1 yr);… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(44 citation statements)
references
References 17 publications
0
43
0
1
Order By: Relevance
“…Microsurgical resection can be undertaken to decompress the nerve, 1,17,27 debulk or strip the tumor from the nerve, 12,17,19 or achieve a complete FNS resection with cable grafting or primary anastomosis. 4,22,25 In a cohort of FNS patients with reasonable facial nerve function, Wilkinson et al compared decompression in 21 patients with observation in 15, and they found no significant difference in facial nerve function between the 2 groups after approximately 3 years of follow-up.…”
Section: Resectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Microsurgical resection can be undertaken to decompress the nerve, 1,17,27 debulk or strip the tumor from the nerve, 12,17,19 or achieve a complete FNS resection with cable grafting or primary anastomosis. 4,22,25 In a cohort of FNS patients with reasonable facial nerve function, Wilkinson et al compared decompression in 21 patients with observation in 15, and they found no significant difference in facial nerve function between the 2 groups after approximately 3 years of follow-up.…”
Section: Resectionmentioning
confidence: 99%
“…Facial nerve function was evaluated by using the House-Brackmann grading system, 16 and hearing function was assessed with the Gardner-Robertson classification. 17 For patients without detailed House-Brackmann or Gardner-Robertson assessments, facial nerve and hearing functions were classified as stable, improved, or worsened by the treating clinicians.…”
Section: Clinical and Neuroimaging Follow-upmentioning
confidence: 99%
“…Total tumor removal and nerve grafting were viewed as the gold standard in the past, but facial nerve recovered to not better than Grade III [2][3][4]. Some studies selected observation, subtotal resection, decompression and stereotactic radiosurgery in a few cases with good facial nerve function, and the results revealed good outcomes [5][6][7][8][9]. In the study of McRackan TR et al [6], they performed subtotal resection on 8 cases, which was defined as tumor removal of greater than 50% with visualized tumor remaining, and the results showed that facial nerve function was improved in 2 patients and facial nerve function was stable in the others, without requirement of further I I TM 30 dB 20 dB No 5 9 FP GG, TS II II TM, MCF Normal Normal No 8 10 CHL, T LS, TS, MS I I TM, MCF 40 dB 25 dB No 9 11 FP, CHL GG, TS, MS III II TM, MCF 55 dB 30 dB No 10 12 FP IAC III III MCF Normal Normal No 11 13 PF GG II I resection of the residual tumors during an average of 44.9 months.…”
Section: Discussionmentioning
confidence: 97%
“…Currently, most authors agree that the ultimate goal is to preserve facial nerve function due to the slow-growing and benign nature of the tumors. Total tumor removal and nerve grafting undoubtedly result in Grade III (House-Brackmann grading system [1]) recovery at best [2][3][4], thus subtotal removal, observation, stereotactic radiosurgery or facial nerve decompression sole is recommended to the patients with good facial nerve function (Grade III or better), since good outcomes of facial nerve could be maintained for a time [5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Traditionally, the management of FNS is complete tumor removal and nerve grafting, but it results in not better than Grade III recovery [3,5,6]. Since FNS are rarely malignant, and brainstem compression and hydrocephalus are quite uncommon, a few authors recommend observation, subtotal resection, decompression or stereotactic radiosurgery instead of immediate surgical removal and nerve grafting when managing those patients who have favorable facial nerve function, so that facial nerve could be maintained at a favorable level for a longer period [9][10][11][12][13].…”
Section: Discussionmentioning
confidence: 99%